Distribution, Polymorphism and Function Characteristics of the GST-Encoding Fhb7 in Triticeae - Xianrui Guo; Mian Wang; Houyang Kang; Yonghong Zhou; Fangpu Han (Plants, 2022)
Encoding a glutathione S-transferase (GST) and conferring resistance to Fusarium head blight (FHB), Fhb7 was successfully isolated from the newly assembled Thinopyrum elongatum genome by researchers, with blasting searches revealing that Thinopyrum gained Fhb7 through horizontal gene transfer from an endophytic Epichloë species. On the contrary, our molecular evidence reveals that the homologs of Fhb7 are distributed commonly in Triticeae. Other than Thinopyrum, the Fhb7 homologs were also detected in four other genera, Elymus, Leymus, Roegneria and Pseudoroegneria, respectively. Sequence comparisons revealed that the protein sequences were at least 94% identical across all of the Fhb7 homologs in Triticeae plants, which in turn suggested that the horizontal gene transfer of the Fhb7 might have occurred before Triticeae differentiation instead of Thinopyrum. The multiple Fhb7 homologs detected in some Triticeae accessions and wheat-Thinopyrum derivatives might be attributed to the alloploid nature and gene duplication during evolution. In addition, we discovered that some wheat-Thinopyrum derivatives carrying the Fhb7 homologs had a completely different reaction to Fusarium head blight, which made us question the ability of the GST-encoding Fhb7 to resist FHB.